Methylation of histone H3 at lysine-37 by Set1 and Set2 prevents spurious DNA replication - Santos-Rosa, Helena (Mol Cell, 2021)
DNA replication initiates at genomic locations known as origins of replication, which, in S. cerevisiae, share a common DNA consensus motif. Despite being virtually nucleosome-free, origins of replication are greatly influenced by the surrounding chromatin state. Here, we show that histone H3 lysine-37 mono-methylation (H3K37me1) is catalyzed by Set1p and Set2p, and that it regulates replication origin licencing. H3K37me1 is uniformly distributed throughout most of the genome but it is scarce at replication origins, where it increases according to the timing of their firing. We find that H3K37me1 hinders Mcm2 interaction with chromatin maintaining low levels of MCM outside of conventional replication origins. Lack of H3K37me1 results in defective DNA replication from canonical origins whilst promoting replication events at inefficient and non-canonical sites. Collectively, our results indicate that H3K37me1 ensures correct execution of the DNA replication programme by protecting the genome from inappropriate origin licencing and spurious DNA replication.